Improving Science Learning Outcomes through an Environment-Based Discovery Learning Model - Hilmiyana Zuhra; Syahidan Nurdin (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to (1) describe teacher activities, (2) describe student activities, and (3) analyze student learning outcomes through the implementation of an environment-based Discovery Learning model. This research is a Classroom Action Research (CAR) conducted in two cycles, involving 34 fifth-grade students as research subjects. Data collection techniques included observation and tests, with instruments in the form of observation sheets for teacher and student activities and learning outcome evaluation questions. The results showed an increase in teacher activity from 76.56% (good category) in Cycle I to 91.40% (very good category) in Cycle II. Student activity also increased from 75.78% (good category) in Cycle I to 90.62% (very good category) in Cycle II. In addition, student learning outcomes improved from 58.82% (not yet complete) in Cycle I to 91.17% (complete) in Cycle II. Thus, the implementation of the environment-based Discovery Learning model was able to create an active, enjoyable, and meaningful learning atmosphere. It can be concluded that the environment-based Discovery Learning model is effective in improving student activities and learning outcomes of fifth-grade students in the IPAS subject at MIN 31 Aceh Utara.